Nutrient germination improves DNA recovery from industrial Bacillus subtilis endospores during qPCR enumeration assays - John P. Gorsuch; Peyton Woodruff (Heliyon, 2019)
Growth-independent microbial enumeration methods such as quantitative PCR require the efficient extraction of genomic DNA from targeted cells. Bacillus endospores are popular inclusions in commercial products due to their hardiness and metabolic dormancy; however, this hardiness is known to render Bacillus endospores resistant to traditional DNA isolation techniques. Metagenomic studies have sought to address this resistance through nutrient-based germination of bacterial endospores in environmental samples. In the present study, we sought to apply this technique to the enumeration of microbial products using an industrial strain of Bacillus subtilis as a model organism. Germination was induced through incubation of axenic spore suspensions in an AGFK-based rich medium. Total spore count, dipicolinic acid release and OD600 absorbance were monitored over time to track the progression of spore populations through the stages of germination and outgrowth. Aerobic plate counts and flow cytometry were used to monitor cell populations for proliferation during the incubation period. Finally, quantitative PCR with taxon-specific primers was used to examine DNA recovery as a function of time. Results show that customized germination protocols, once appropriately validated for the species and product matrix under consideration, can result in more efficient DNA extraction and thus lower limits of detection for qPCR assays targeting industrial Bacillus endospores in microbial products.